2020
DOI: 10.1200/po.19.00354
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Incidental Germline Findings Identified In the Context of Clinical Whole Exome Sequencing for Guiding Cancer Therapy

Abstract: PURPOSE Identification of incidental germline mutations in the context of next-generation sequencing is an unintended consequence of advancing technologies. These data are critical for family members to understand disease risks and take action. PATIENTS AND METHODS A retrospective cohort analysis was conducted of 1,028 adult patients with metastatic cancer who were sequenced with tumor and germline whole exome sequencing (WES). Germline variant call files were mined for pathogenic/likely pathogenic (P/LP) vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…These findings indicate that the existing guidelines and consensus could miss those patients who have an HCRC. The results were consistent with previous studies indicating that following clinical guidelines would miss more than half of germline variants based on pan‐cancer analysis 14,15 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings indicate that the existing guidelines and consensus could miss those patients who have an HCRC. The results were consistent with previous studies indicating that following clinical guidelines would miss more than half of germline variants based on pan‐cancer analysis 14,15 …”
Section: Discussionsupporting
confidence: 92%
“…However, whether CRC tumors without matched normal tissue/WBCs could be used to predict germline variants and diagnose HCRC using next‐generation sequencing (NGS) remains elusive. Several previous studies have demonstrated that guidelines for cancer genetic testing based on family history may miss clinically actionable genetic changes 14,15 . A pan‐cancer study has indicated that more than 50% of cancer patients harbor P/LP germline variants without a family history or phenotype 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Tumor next generation sequencing (NGS) has become commonplace in routine clinical practice for patients with a variety of malignancies to help identify potential drug targets. We, and others, have demonstrated that in the process of tumor NGS approximately 3–13% of patients are found to harbor incidental germline pathogenic variants 1 7 . While not the goal of tumor NGS, these findings can have major implications for healthy family members 8 .…”
Section: Introductionmentioning
confidence: 86%
“…Recent studies have shown that 10 to 15% of patients with advanced malignancies of many types have a pathogenic germline alteration. 4,5 Germline DNA is usually acquired from peripheral blood, a buccal swab, or saliva collection and is therefore readily available. This is advantageous because it does not require a biopsy to identify relevant alterations.…”
Section: Germline Testingmentioning
confidence: 99%